Relationships between technology usage, curiosity, self-efficacy and misbehaviour among preschoolers from teachers’ perspectives in Selangor, Malaysia - Tan, Yen Teng (2019)
Misbehaviour is a significant problem among preschoolers. This problem is common and frequently reported by the preschool teachers. Past studies found that preschoolers who misbehave are at high risk of emotional behavioural disorder and often facing difficulties in study. Understanding the factors contributing to preschooler’s misbehavioural is vital for effective intervention. Therefore, this study was designed to investigate the relationships between technology usage, curiosity, and misbehaviour among preschoolers from teachers’ perspectives in Selangor, Malaysia. In addition, this study also examined the role of self-efficacy as mediator on the relationships between technology usage and curiosity on preschooler’s misbehaviour. The present study employed Bandura’s social cognitive theory and the ecological techno-subsystem in providing a valid basis for explaining and predicting misbehaviour among preschoolers in Selangor, Malaysia.